A Qualitative Study on Curriculum Supervision and Learning Modalities in the Time of Pandemic: Basis on the Proposed Innovative Supervisory Framework - Aquino, John Michael Del Rosario (Jurnal Pendidikan Progresif, 2023)
A Qualitative Study on Curriculum Supervision and Learning Modalities in the Time of Pandemic: Basis on the Proposed Innovative Supervisory Framework. This study examines the challenges posed by the pandemic to instructional leaders and their ability to supervise teachers, focusing on the university context. Using a phenomenological approach, 6 instructional leaders were interviewed through a face-to-face questionnaire to uncover the supervision models, processes of supervising teachers, different learning modalities, and supervisory framework. The results revealed that the synchronous class was most effective among the three modalities used: synchronous, asynchronous, and modular. Furthermore, a differentiated supervision model was constructed based on the practices of instructional leaders, and a framework was proposed for use in other schools. The implications of this research are that instructional leaders should be aware of the various supervision models, processes, and learning modalities available in order to effectively respond to and cope with the crisis. Additionally, other schools can employ alternative supervision models by investigating the characteristics that affect supervision. Keywords: leadership, curriculum supervision, new normal education, pandemic.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202313